Fus1 KO Mouse As a Model of Oxidative Stress-Mediated Sporadic Alzheimer's Disease: Circadian Disruption and Long-Term Spatial and Olfactory Memory Impairments - Coronas-Samano, Guillermo; Baker, Keeley L.; Tan, Winston J. T.; Ivanova, Alla V.; Verhagen, Justus V. (Frontiers in Aging Neuroscience, 2016)
Insufficient advances in the development of effective therapeutic treatments of sporadic Alzheimer's Disease (sAD) to date are largely due to the lack of sAD-relevant animal models. While the vast majority of models do recapitulate AD's hallmarks of plaques and tangles by virtue of tau and/or beta amyloid overexpression, these models do not reflect the fact that in sAD (unlike familial AD) these genes are not risk factors per se and that other mechanisms like oxidative stress, metabolic dysregulation and inflammation play key roles in AD etiology. Here we characterize and propose the Fus1 KO mice that lack a mitochondrial protein Fus1/Tusc2 as a new sAD model. To establish sAD relevance, we assessed sAD related deficits in Fus1 KO and WT adult mice of 4-5 months old, the equivalent human age when the earliest cognitive and olfactory sAD symptoms arise. Fus1 KO mice showed oxidative stress (increased levels of ROS, decreased levels of PRDX1), disruption of metabolic homeostasis (decreased levels of ACC2, increased phosphorylation of AMPK), autophagy (decreased levels of LC3-II), PKC (decreased levels of RACK1) and calcium signaling (decreased levels of Calb2) in the olfactory bulb and/or hippocampus. Mice were behaviorally tested using objective and accurate video tracking (Noldus), in which Fus1 KO mice showed clear deficits in olfactory memory (decreased habituation/cross-habituation in the short and long term), olfactory guided navigation memory (inability to reduce their latency to find the hidden cookie), spatial memory (learning impairments on finding the platform in the Morris water maze) and showed more sleep time during the diurnal cycle. Fus1 KO mice did not show clear deficits in olfactory perception (cross-habituation), association memory (passive avoidance) or in species-typical behavior (nest building) and no increased anxiety (open field, light-dark box) or depression/anhedonia (sucrose preference) at this relatively young age. These neurobehavioral deficits of the Fus1 KO mice at this relatively young age are highly relevant to sAD, making them suitable for effective research on pharmacological targets in the context of early intervention of sAD.